Eficiência de diferentes ramais de pulverização e volumes de calda no controle de Brevipalpus phoenicis na cultura do café - Fernandes, Ana Paula [UNESP]; Ferreira, Marcelo Da Costa [UNESP]; Oliveira, Carlos Amadeu Leite De [UNESP] (Sociedade Brasileira De Entomologia, 2010)
Efficiency of different spraying lances and spraying volumes on the control of Brevipalpus phoenicis in coffee crops. The mite Brevipalpus phoenicis is found on coffee plantations in Brazil since the 1950's. Responsible for indirect losses due to its role as vector of a virus disease, this mite species often requires control measures, the most common based on mitecide spraying. It was evaluated the mortality of B. phoenicis due the coverage of spraying liquid applied on coffee plants, with two types of lances used in air assisted sprayers and four spraying volumes. Treatments were applied with mitecide abamectin (Vertimec 18 CE® at 0.4 L per hectare), in volumes of 250, 400, 550 and 700 L per hectare, with two types of lances for the nozzles. The control efficiency against B. phoenicis, deposition and coverage by spray liquid on coffee plants was evaluated. Experimental delineation was in randomized blocks, with eight treatments plus a check plot in four replications. The statistical analysis was carried in a factorial scheme 2x4+1. No significant differences in the number of mites were found between treatments. As regards spraying liquid deposition, it was observed an increment with increasing spraying volumes, with the plant tops showing the best deposition of spraying liquid. The duplication of the lances (nozzle branches) resulted in a significant increase in control efficiency for B. phoenicis compared with conventional branch and with check plot, without dependence of spraying volume.

O ácaro Brevipalpus phoenicis é encontrado nos cafezais do Brasil desde a década de 50. Responsável por perdas indiretas por ser o vetor de uma doença virótica requer constantes medidas de controle, sendo a mais utilizada baseada na pulverização de acaricidas. Avaliou-se a mortalidade do ácaro B. phoenicis em função da cobertura de calda aplicada em plantas de café, com dois tipos de ramais utilizados em pulverizadores de jato transportado e quatro volumes de aplicação. O produto utilizado para o trabalho foi o acaricida abamectina (Vertimec 18 CE® na dose de 0,4 L/ha). Os tratamentos utilizados foram a aplicação do acaricida abamectina, nos volumes de 250, 400, 550 e 700 L/ha, com dois tipos de ramais de bicos. Em cada tratamento foram avaliadas a eficiência de controle de B. phoenicis, a deposição e a cobertura da calda nas plantas de café. O delineamento experimental utilizado foi em blocos casualizados, com oito tratamentos mais uma testemunha e quatro repetições. A análise estatística foi realizada no esquema fatorial 2x4+1. Verificou-se que não houve diferenças significativas no número de ácaros encontrados entre os tratamentos. Para a deposição de calda, observou-se um aumento em função do volume de aplicação, sendo que a parte superior das plantas apresentou maior deposição de produto. A duplicação dos ramais resultou em um aumento significativo da eficiência de controle de B. phoenicis comparado ao ramal convencional e à testemunha, independe do volume de aplicação entre os limites avaliados.
Efficiency of different spraying lances and spraying volumes on the control of Brevipalpus phoenicis in coffee crops
Keywords: Chemical control; droplet size; sprayer; spraying nozzles; Controle químico; diâmetro de gotas; pulverizador; pontas de pulverização